The profile of credit defaulters in Bank Rakyat Masjid Tanah / Norhamizah Mohd Noor - Mohd Noor, Norhamizah (Faculty of Business and Management, 2004)
Malaysian life style is not much different with others develop countries. There are many type of products offer in the market such as automobile, housing estate, education, vacation, information technologies, fashion, entertainment and others. To own the products people must have money. But not many people can afford to pay it cash. Needs and wants have no border but people have limited resources, so that Bank offer debt market to consumer to satisfy what people needs and wants. The availability of loan from credit department of the bank allows us to have a better life and higher standard of living. (Sheer 1999). From the consumer perspective, loan offer by bank services help them in many way. But from the bankers' point of view, once the loan delivered, the bank will face the risk that probability the borrowers not pay the debt. This means each lender will be permitted full discretion, at its own risk, to assess the credit risk of each prospective borrower.